Star wars: tales from the death star ebook - Scott, Cavan (Star Wars: Tales From The Death Star (2023)., 2023)
"That's no moon…"Even scattered and destroyed, the ruins of the Death Star are a sinister place.From the destruction of Alderaan to the shadow of the Forest Moon, alien creatures, phantom star ships, deadly artifacts, and vengeful spirits all stalk the halls of the infamous space station, as writer Cavan Scott (Tales from the Rancor Pit, Star Wars: The High Republic) and an all-star team of artists (Eric Powell, Soo Lee, Vincenzo Riccardi, Ingo Römling, & Juan Samu) reveal the hidden evils that lurked within charred remains of the ultimate firepower in the universe.